Investigation of the effect of some geomorphologic features of Joghatai mountains on water quality changes in terms of chromite - ali akbar shayan yeganeh; mina firoz yazdi; javad jamalabadi (تحقیقات کاربردی علوم جغرافیایی)
Water is one of the most vital human needs. Chromium is one of the heavy metals that causes water pollution in different regions. The studied area is Joghatai Mountains and Davarzan, Khoshab, Joghatai, Joveyn and Sabzevar plains of Razavi Khorasan Province. This research has studied, analyzed water pollution with the element of chromium as well as the impact of lithology mountains Joghatai, on the quality of water in the region from the point of view of chromit. In this research, 13 samples were collected and tested by atomic spectrometer method.To check the amount of chromium present in them by comparing the findings with standard limits. The results of this study show that the amount of chromium in the selected water sources varies from 1.2 to 1.3 mg / L. Geochemical samples vary from 210 ppm to 4700 ppm. The lithology of the region especially the chromium mines has affected the quality of water but the density of faults and fans did not affect the amount of dissolved chromite. The effect of the slope of the geological layers is positive and the role of acidity in the pollution is poor. Finally, the amount of chromium in some samples is higher than the standard limit and should be considered by the custodians.